British Workers and the Independent Labour Party, 1888-1906 - Naylor, James (Labour / Le Travail, 1986)
This article reviews the book, "British Workers and the Independent Labour Party, 1888-1906," by David Howell.
Keywords: BRITISH Workers & the Independent Labour Party 1888-1906 (Book); HOWELL; David; INDEPENDENT Labour Party (Great Britain); Nonfiction; REVIEWS; books